Marital intimacy of Filipino couples with grade school children - Lim, Sarah Jane R.
ABSTRACT This study sought to identify the factors that influence the intimacy of married Filipino couples with grade school children and describe the intimacy of these couples in the aspects of Cognitive, Affective, and Physical Intimacy, Commitment and Mutuality. Ten married couples that had first-born children who were in grade school were interviewed. The husbands and the wives were interviewed separately and asked to identify factors that influence their intimacy and describe their intimacy. The interviews were transcribed, coded, and grouped into themes. Majority of the couples stated several factors that were classified under personal, religious, occupational, other family, and familial factors. The presence of intimacy was found in most of the couples, which had a mixture of similar and varying answers.